Evolutionary and phylogenetic analyses of 11 Cerasus species based on the complete chloroplast genome - Wan, Tian; Qiao, Bai-xue; Zhou, Jing; Shao, Ke-sen; Pan, Liu-yi; An, Feng; He, Xu-sheng; Liu, Tao; Li, Ping-ke; Cai, Yu-liang (Frontiers in Plant Science, 2023)
The subgenus Cerasus, one of the most important groups in the genus Prunus sensu lato, comprises over 100 species; however, the taxonomic classification and phylogenetic relationships of Cerasus remain controversial. Therefore, it is necessary to reconstruct the phylogenetic tree for known Cerasus species. Here, we report the chloroplast (cp) genome sequences of 11 Cerasus species to provide insight into evolution of the plastome. The cp genomes of the 11 Cerasus species (157,571–158,830 bp) displayed a typical quadripartite circular structure. The plastomes contain 115 unique genes, including 80 protein-coding genes, four ribosomal RNAs, and 31 transfer RNAs. Twenty genes were found to be duplicated in inverted repeats as well as at the boundary. The conserved non-coding sequences showed significant divergence compared with the coding regions. We found 12 genes and 14 intergenic regions with higher nucleotide diversity and more polymorphic sites, including matK, rps16, rbcL, rps16-trnQ, petN-psbM, and trnL-trnF. During cp plastome evolution, the codon profile has been strongly biased toward the use of A/T at the third base, and leucine and isoleucine codons appear the most frequently. We identified strong purifying selection on the rpoA, cemA, atpA, and petB genes; whereas ccsA, rps19, matK, rpoC2, ycf2 and ndhI showed a signature of possible positive selection during the course of Cerasus evolution. In addition, we further analyzed the phylogenetic relationships of these species with 57 other congenic related species.Through reconstructing the Cerasus phylogeny tree, we found that true cherry is similar to the flora of China forming a distinct group, from which P. mahaleb was separated as an independent subclade. Microcerasus was genetically closer to Amygdalus, Armeniaca, and Prunus (sensu stricto) than to members of true cherry, whereas P. japonica and P. tomentosa were most closely related to P. triloba and P. pedunculata. However, P. tianshanica formed a clade with P. cerasus, P. fruticosa, P. cerasus × P. canescens ‘Gisela 6’, and P. avium as a true cherry group. These results provide new insights into the plastome evolution of Cerasus, along with potential molecular markers and candidate DNA barcodes for further phylogenetic and phylogeographic analyses of Cerasus species.